Sonographic measurement of spleen dimensions in healthy adults in North-Western Nigeria - NJBCS, Author (Nigerian Journal of Basic and Clinical Sciences, 2026)
Introduction:In the last two decades sonography has become the most important imaging modality for the study of the spleen. Different studies have been conducted in different parts of the world so as to determine the normal reference values of splenic dimension using ultrasound scan in healthy adults, and the values obtained have been diverse, thus prompting more work that tends to establish normal values for different regions based on geographic and racial differences.Materials and Methods:A prospective study of normal spleen dimensions using ultrasound in 400 Nigerian adults at Aminu Kano Teaching Hospital was conducted. Sonographic measurement of splenic dimensions was performed with the patient in supine and right lateral decubitus position. Height and weight were measured using the standard anthropometric technique. The data were analysed using computer-based SPSS Version 16.0 software for Windows (SPSS Inc., Chicago, IL, USA).Results:There were 212 males and 188 females, their age ranged between 20 and 70 years. The mean age of the subjects and (±standard deviation) were 33.0 years (±12.0), mean height was 1.64 m (±0.1) and mean weight was 61.4 kg (±11.0). The mean splenic length, width and depth for the subjects studied were 101.6 mm (±13.7), 46.8 mm (±8.2), and 86.8 mm (±12.7), respectively.Conclusion:The mean spleen dimensions obtained in this study were similar to those obtained in other regions of Nigeria but slightly lower than those reported from studies among Caucasians confirming the need for normal values for each region. There was positive correlation between subjects height and weight with splenic length (P< 0.001 andP< 0.001), depth (P< 0.01 andP< 0.001) and width (P< 0.01 andP< 0.001).